Phytochemical composition and bioactivities of Satureja montana L. and Satureja hortensis L.: Culinary herbs with antidiabetic, anticholinesterase, and antioxidant potential - Furkan Coban; Yuzhou Lan; Gül Yetisgin; Hafize Yuca; Bilge Aydın; Hilal Angın; Betül Demirci; Songül Karakaya (PLoS ONE, 2025)
The increasing global burden of oxidative stress-related conditions, diabetes, and neurodegenerative disorders underscores the urgent need for multi-targeted, plant-based therapeutic agents. In this context, the present study aimed to evaluate the antidiabetic, antioxidant, and neuroprotective properties of various Satureja hortensis and Satureja montana extracts and essential oils. In vitro biological activities were assessed through α-glucosidase, acetylcholinesterase (AChE), and butyrylcholinesterase (BChE) inhibition assays, along with DPPH• and ABTS• ⁺ radical scavenging assays. At a concentration of 100 µg/mL, S. hortensis root methanol extract (ShRME) and herb water extract (ShHWE) exhibited strong α-glucosidase inhibitory activity (69.88% and 71.23%, respectively). Conversely, S. montana herb water extract (SmHWE) and methanol extract (SmHME) showed the highest DPPH• radical scavenging activity (36.28% and 24.37%, respectively). S. montana essential oil (SmEO) demonstrated notable inhibition of AChE (32.58%) and BChE (41.62%) at 1000 µg/mL, while S. hortensis essential oil (ShEO) inhibited BChE by 44.39%. GC-MS analysis revealed that SmEO primarily contained carvacrol (43.72%), γ-terpinene (17.24%), and p-cymene (14.56%), while ShEO was rich in thymol (39.84%), γ-terpinene (20.16%), and p-cymene (13.72%). These phenolic monoterpenes are likely contributors to the observed antioxidant and cholinesterase inhibitory activities. Principal component analysis explained 74.8% of the total variance and clearly separated the samples based on their activity profiles. Extracts were closely associated with glucose-regulating effects, while essential oils clustered with enzyme-inhibiting neuroprotective activities. These findings highlight the multifunctional therapeutic potential of Satureja species and support their further investigation as candidates for the development of plant-derived agents against oxidative stress, diabetes, and neurodegenerative diseases.